All-inclusive coral reef restoration: How the tourism sector can boost restoration efforts in the caribbean - Blanco-Pimentel, Macarena; Evensen, Nicolas R.; Cortés-Useche, Camilo; Calle-Triviño, Johanna; Barshis, Daniel J.; Galván, Victor; Harms, Erika; Morikawa, Megan K. (Frontiers in Marine Science, 2022)
Following a strong decline in the health of Caribbean coral reefs in the 1970s, disease outbreaks, overfishing, and warming events have continued to push these reefs towards a point of no return. As such, researchers and stakeholders have turned their attention to restoration practices to overcome coral recovery bottlenecks on Caribbean reefs. However, successful restoration faces many challenges, including economical and logistical feasibility, long-term stability, and biological and ecological factors yet to fully understand. The tourism sector has the potential to enhance and scale restoration efforts in the Caribbean, beyond simple financial contributions. Its strengths include long-term presence in several locations, logistical and human resources, and a business case focused on preserving the ecosystem services on which it depends. Here, we present the restoration program of Iberostar Hotels and Resorts which includes a scientific team that incorporates science-based solutions into resort operations to promote reef resilience in the face of climate change. We exemplify the potential of our program to scale up science-based reef restoration in collaboration with academia, local community, and government by presenting the first utilization of the Coral Bleaching Automated Stress System (CBASS) in Latin America and the Latin American Caribbean, with the aim of applying findings on coral thermotolerance directly to Iberostar’s reef restoration program across the Caribbean. This program presents a new model for tourism involvement in coral restoration and illustrates its capacity to scale up existing restoration practices by utilizing the strengths of the sector while maintaining science-based decision making.